Neologismo em foco : inovações lexicais no Jornal Massa! - Gama, Vanessa Oliveira Silva (2017)
Change is undoubtedly a fundamental phenomenon, which allows the renewal and preservation of the language over time. As a product and producer of a given society, it is natural for language to accompany her dynamism. Linguistic changes take place primarily in speech, especially in informal contexts, where there is a lower level of monitoring and a reduced distance between the speaker and his interlocutor. It is in everyday speech that the sender has the freedom to access the potentialities of the system and to dare in the elaboration of new words, aiming at the improvement of the communication. This process of linguistic creation and renewal is called neology. Its product, in turn, is called the neologism. In this perspective, when adopting the neologism as object of study, we look for a corpus that would allow the extraction of a significant number of neological lexias present in the present Portuguese. Thus, we selected 70 copies of the popular Bahia Massa! newspaper, referring to the months of January to March of 2015, which present in their headlines, calls and titles several neological lexias constant in the speech of their public-reader. We base the research on the analysis and classification of the 203 new words detected, based on theoretical studies based on neology and lexicology of the Portuguese language. The identification of the neological character was made from current dictionaries, such as Houaiss (2009), Aurélio (2010) and Dicio (online). The parameter for the organization of the data consisted of: a) grammatical classification, b) meaning, c) type of formation process, d) contexts in which they appear along the copies. This procedure allowed us to observe that the most frequent type of neologism in the corpus is the formal one, and the most productive lexical process is the semantic one. In addition, it was possible to verify that the creation of neologisms by the speakers occurs in a systematic way, in informal contexts of communication and with a definite purpose, that is, of propagating ideas and concepts.